Portable oil skimmer development via Kansei Engineering with analytical hierarchy process for oil spillages recovery - Ramanathan, Rprakash (2024)
The alarming impact of oil spills on the environment necessitates immediate control and recovery measures. There are different types of recovery method such as mechanical method, chemical, in-situ burning and biological method. The mechanical technique consists of boom and skimmer. The boom and skimmer are used together for the oil recovery process. However, the integration of boom presents containment challenges, and the current market of skimmers are heavy-duty and large-sized skimmers causes deployment difficulties in confined areas such as lakes, rivers, ponds, and treatment plants. Furthermore, during the design stages, the focus has traditionally been on technical requirements while neglecting user requirements. However, the dependency solely on technical requirements overlooks critical design factors such as robustness, safety, ease of use, and portability. Therefore, the objective of this reseach is to design and develop the Portable Oil Spill Skimmer (POSS) with consideration of user requirement during the initial design phase. To bridge this gap, Kansei Engineering method was employed to gather both user and technical requirements for the POSS during the early design process. Analysed data obtained from Kansei Engineering led to the identification of crucial design elements that must be considered in the design of a portable oil spill skimmer. Subsequently, five design concepts were generated, and the Analytical Hierarchy Process (AHP) was utilised for decision-making process. The AHP result indicates that design (D3) identified as the best design. Result of AHP was validated using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The robustness of the AHP result was confirmed through Sensitivity Analysis. Moreover, design optimisation was conducted in simulations analysis to analyse the proposed design before fabrication. Structural analysis simulations revealed a maximum stress of 23.27 MPa, maximum deformation of 9.8169 × 10-5 mm/mm, and a safety factor of 12.74 indicating that POSS has a sturdy stucture. Additionally, Computational Fluid Dynamics (CFD) simulations demonstrated that the propellers could generate 72.8 N of thrust force, capable of overcoming the hull drag of 27.11 N, indicating the skimmer's maneuverability. Further simulation was conducted to implement baffles in the oil tank to mitigate oil sloshing effects. The result indicates that there was a of 67.21% torque reduction in sloshing compared to an oil tank without baffles. The portability characteristics of the POSS satisfies 7 portable meta-heuristics and heuristics standard. Besides that, the speed of POSS was experimented, which indicates that the POSS is capable to travel at a speed of 3.72 Knots. Last but not least, the oil recovery capacity of the POSS was analysed and efficiently recovers at a rate of 8 ml/min with 90 % efficiency. As a future recommendation, it is feasible that POSS to be further developed with solar panels instead of batteries for optimum performance.